Multi‐model switching‐based fault tolerant control for planar robot manipulators. Issue 1 (1st January 2020) - Meng, Yajun; Yang, Hao; Jiang, Bin
Abstract : This study addresses the fault‐tolerant tracking control issue for a class of planar manipulators with various actuator and sensor faults. Firstly, a set of linear models are constructed to approximate the original non‐linear model at the different joint angular positions, which explicitly reveal the coupling effects among sub‐manipulators. Secondly, a family of decentralised fault‐tolerant controllers are proposed with each one being related to one linear model respectively, which does not require the information exchange among sub‐manipulators and thus lightens the communication burden. Finally, a switching law is proposed among controllers such that the system remains stable in the presence of controller switching. An example of a three‐link planar robot manipulator is taken to illustrate the effectiveness of the proposed methods.